Identification of Human Resource Management Functions in Medium Businesses - Fabiani Sofie; Sisca Eka Fitria (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
The Indonesian economy is dominated by MSMEs (Micro, Small and Medium Enterprises). MSMEs have a very important role because it can absorb labor and also contribute to GDP (Gross Domestic Product). CV. Kota Agung is one of MSME which has been established since 2006. This company also contribute to environmental sustainability by being a pioneer of tree planting in Indonesia. However, the company is experiencing problems with urgent human resource management to be addressed immediately. This study aims to determine the managerial and operational functions of human resource management applied in the CV. Kota Agung. In addition, this study also aims to determine which functions should be fixed. This study conducted interviews with directors, deputy directors, and branch heads of CV. Kota Agung to collect the necessary data and use using qualitative methods. The results of this study indicate that CV. Kota Agung has not implemented the overall managerial function of human resource management. Planning, organizing, controlling has not been well implemented. In addition, CV. Kota Agung also has not implemented the operational function of human resource management as a whole. Procurement, development, maintenance and dismissal compensation shall be applied with good consideration.